Problematika Pelaksanaan Hak Tanggungan Elektronik di Kantor Pertanahan di Kabupaten Pinrang - Amriana Amirullah; Muhammad Sabir; Aksah Aksah; Lia Trizza FA; Kairuddin Kairuddin (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
This study aims to examine and analyze the implementation of the Electronic Mortgage (HT-el) at the Pinrang Regency Land Office based on Minister of Agrarian Affairs and Spatial Planning/National Land Agency Regulation No. 5 of 2020 and to identify the challenges encountered in its implementation. This study is normative-empirical research employing both a legal and a social approach. Data sources consist of primary and secondary data obtained through observation, interviews, and documentation. Data analysis was conducted using observational-sensory and theoretical-rational methods, applying a reasoning model that first utilized inductive logic followed by deductive logic. The results of the study indicate that the implementation of the electronic mortgage registration system (HT-el) at the Pinrang Regency Land Office has been carried out in accordance with the provisions of Minister of Agrarian Affairs and Spatial Planning/National Land Agency Regulation No. 5 of 2020. The application of the electronic system has improved efficiency, transparency, and accountability, while also providing convenience and certainty in the registration services for mortgage rights. The challenges encountered include legal obstacles (regulatory adjustments), technical issues (system and internet network disruptions), administrative hurdles (incomplete or non-compliant required documents), and sociological factors (differences in users’ levels of understanding and ability to operate the HT-el system), but these did not hinder the overall implementation of HT-el, as they could be overcome through coordination among stakeholders, human resource capacity building, and system improvements.